Association Between History of Gestational Diabetes Mellitus and the Risk of Arthritis in Women - Mao, Yuanyuan; Hu, Wenbin; Xia, Bin; Liu, Li; Liu, Qin (Frontiers in Public Health, 2022)
Objective: The association between gestational diabetes mellitus (GDM) and the risk of arthritis has not been reported. GDM increases the risk of long-term complications including diabetes and metabolic syndrome that are positively associated with the risk of arthritis. This study aimed to explore the association between GDM and the risk of arthritis. Methods: Women (age ≥ 20 years) who had delivered at least one live birth were included from the 2007–2018 National Health and Nutrition Examination Survey cohort (N=11,997). Patients who had a history of GDM and arthritis were identified by in-home interview. Subgroup analyses were conducted by arthritis types and status of obesity, current diabetes, metabolic syndrome, smoking, alcohol drinking and physical activity. Results: GDM was associated with increased odds of arthritis [multivariable-adjusted odds ratio (95% confidence interval): 1.31 (1.06-1.62)], and the result was similar in sensitivity analysis with further adjustment for metabolic syndrome [1.30 (1.05-1.60)]. In subgroup analyses, GDM was associated with increased odds of osteoarthritis [1.47 (1.05-2.06)], while no association was observed with rheumatoid arthritis [1.04 (0.69-1.57)] and other types [1.26 (0.94-1.68)]. GDM was associated with increased odds of arthritis in women without metabolic syndrome [1.34 (1.00-1.78)] and diabetes [1.35 (1.03-1.76)], in obese individuals [1.64 (1.24-2.16)], current/former smokers [1.43 (1.05-1.95)] and current drinkers [1.76 (1.00-3.14)], and in individuals engaging in higher levels of physical activity [1.53 (1.06-2.20)]. Conclusions: GDM was associated with increased odds of arthritis, and the association was independent of type 2 diabetes and metabolic syndrome.